THE EFFECT OF GROSS DOMESTIC PRODUCT AND INTEREST RATES ON CREDIT DEMAND - Saputri, Erliana Eka (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
In Indonesia, bank banking is very meaningful for example in terms of development. This is because banks can influence the overall economic cycle. The increase in demand for bank credit has resulted in increased purchasing power, increased business enthusiasm and an investment bonus. Which in conclusion will produce the Multiplier Effect. The multiplier effects include the addition of new business establishments, additional workforce, increased demand for raw materials, increased production output and increased purchasing power which will affect future economic growth. The research has the objective of explaining the Effect of Gross Domestic Product and Interest Rates on Credit Demand. This research uses descriptive quantitative research methods and uses multiple regression which can see the effect of Gross Domestic Product and Interest Rates on Credit Demand. In this study, it was found that the Gross Domestic Product has an influence on the demand for credit, while the interest rate has no influence on the demand for credit.